DESCRIPTION OF MEDICINAL PROPERTIES AND SIGNIFICANCE OF SOME MEDICINAL PLANTS BELONGING TO APECEAE FAMILY. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article talks about some medicinal plants that are considered representatives of the Apiceae family and are widely used in scientific medicine.